2009
DOI: 10.1007/978-1-4419-5692-7_34
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway and Abdominal Motor Output During Sneezing: Is the In Vivo Decererate Rat an Adequate Model?

Abstract: While numerous studies have focused on identifying and characterizing the neural mechanisms mediating upper airway defense reflexes in the anesthetized or decerebrate adult cat, little is known about these behaviors in in vivo rodent models. The current study was undertaken to investigate whether the in vivo decelerate adult rat might serve as an acceptable model for studying these behaviors. To begin to address this possibility, we examined multiple respiratory motor activities in response to mechanical stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…; Ono et al . ). However, in our in vitro experiments, we verified that addition of ionotropic receptor antagonists (GABA, glutamate and glycine) to the bathing solution did not abolish the activity of most tonically active motoneurons, indicating the contribution of intrinsic properties to the excitability of these cells or the involvement of other neurotransmitters (Bayliss et al .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…; Ono et al . ). However, in our in vitro experiments, we verified that addition of ionotropic receptor antagonists (GABA, glutamate and glycine) to the bathing solution did not abolish the activity of most tonically active motoneurons, indicating the contribution of intrinsic properties to the excitability of these cells or the involvement of other neurotransmitters (Bayliss et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated that expiratory muscles are recruited in some diseases, such as hypertension and heart failure, as well as in hypoxic environments (Giordano, 2005;Bosc et al 2010;Haupt et al 2012), to generate active expiration. However, the cellular mechanisms related to how expiratory motoneurons changes their electrophysiological properties to ensure an effective muscle contraction are relevant not only to diseased states, but also to physiological conditions with respect to avoiding large respiratory variability, such as during coughing, sneezing, speaking (Hoit et al 1988;Ono et al 2010), physical activity (Willett et al 2001) or even in the REM sleep epochs (Andrews & Pagliardini, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations